Creative Experience: A Non-Standard Definition of Creativity. Issue 2 (3rd April 2021) - Glăveanu, Vlad P.; Beghetto, Ronald A.
ABSTRACT: We propose a working definition of creative experience that involves principled engagement with the unfamiliar and a willingness to approach the familiar in unfamiliar ways. In other words, a creative experience can be defined as novel person world encounters grounded in meaningful actions and interactions, which are marked by the principles of: open-endedness, nonlinearity, pluri-perspectives and future-orientation. Our definition shares some similarities with the standard definition offered by Runco and Jaeger in that it still recognizes the importance of novelty and effectiveness but goes beyond that definition by asserting that novelty and meaningfulness are not sufficient for characterizing creative experiences. Indeed, as we will discuss, creative experiences are marked by a set of principles that we argue inhere in all creative actions.